Survival of preterm babies beyond the neonatal period - Lamis Aziz Hameed (The Medical Journal of Basrah University, 2016)
Background: Preterm birth is a significant cause of infant deaths particularly during the neonatal period. Study of these births may assist in predicting the survival of those born preterm, and in turn may help in reducing the causes and undesired outcomes. Objective: This study was designed to explore the chance of survival among babies admitted to intensive care units in Basrah Maternity and Children Hospital. Method: The study was a follow up study carried out on 440 babies who were born preterm and were admitted for reasons related to their prematurity to neonatal intensive care units in Basrah maternity and children hospital in 2012, of whom 408 were successfully followed up until the end of the neonatal period (birth to 28 days). Results: Most of the babies were males (58.8%), singleton (93.1%), delivered by normal vaginal delivery (74.01%), moderately preterm (53.4%) and of birth weight range 1500- < 2500 grams(62.5%). Logistic regression analysis to identify independent predictors of survival showed that neonatal outcome (the probability of surviving the neonatal period) was significantly and independently related to birth weight and gestational age. Other variables [sex, type of delivery and type of birth(single, twin and multiple] could not significantly predict survival in the present study. Conclusions: It is concluded that the problem of neonatal mortality in Basrah is similar to that reported for other developing and neighboring countries. In our study the neonatal mortality rate was 27.94%, mostly in the first 24 hours of life. Two significant predictors could be identified as undesired predictors of survival; namely; low birth weight and shorter gestational age. We highly recommend a larger scale study on issue of neonatal survival. Perhaps improved care of mothers and neonates reduce the risk of both preterm birth and neonatal death.